Organizational politicization and its relationship to dysfunction among educational supervisors - Dr. Saad Naeem Radwi (Journal of College of Education, 2025)
The study aimed to identify the level of organizational politicization and its relationship to dysfunction among educational supervisors from the point of view of school principals and their assistants in the preparatory stage in Wasit Governorate. To achieve this, the descriptive correlational approach was adopted, and the study tools were two questionnaires that were applied to a sample drawn through the Richard Geiger equation, the Krajci and Morgan equation, the Herb Arkin equation, the Robert Mason equation, and the Stephen Thompson equation. It was found that the size of the study sample was (152) principals and their assistants, during the second semester of the academic year (2024-2025), and using the statistical package (SPSS), the data were processed statistically, and the results showed the availability of organizational politicization and dysfunction among educational supervisors from the point of view of school principals and their assistants in the preparatory stage in Wasit Governorate. It was also noted that there is a direct relationship between organizational politicization and dysfunction among educational supervisors from the point of view of school principals and their assistants in the preparatory stage.
Keywords: organizational politicization , dysfunction , educational supervisors